EARLY TOXICOSIS IN PREGNANCY - Abdiyeva Setorakhan Ahmadjon qizi (Scholar Express Journals, 2023)
As a rule, pregnancy is a version of the physiological state of the body, it does not bother the woman and she feels well. It appeared in the early period and is used to identify signs of pregnancy, vomiting and other symptoms, in fact, they say that not everything is safe in the body of the future mother.
Keywords: pregnancy; toxicosis; mother and baby